A checklist of the protozoan and metazoan parasites of European eel (Anguilla anguilla): checklist of Anguilla anguilla parasites. (25th November 2009) - Jakob, E.; Walter, T.; Hanel, R.
Summary: A comprehensive literature review on prevalence and distribution of parasites of the European eel ( Anguilla anguilla ) in European waters was conducted to set a baseline for future trend analyses and biodiversity considerations. The resulting checklist compiled from peer reviewed journals as well as grey literature including scientific reports, conference contributions, PhD theses and own survey data includes all protozoan and metazoan parasites of the European eel from freshwater, brackish and marine habitats. Parasites are arranged according to phylum and family. Species within families are listed alphabetically. Infected host organs, recorded habitats, localities, countries and literature citations are provided for each species. A total of 161 parasite species ⁄ taxa from 30 countries are listed. With the trypanorhynch cestode Tentacularia coryphaenae a new host record could be documented. Furthermore, three new locality records of parasitic nematodes could be added based on own survey data: Anisakis simplex from an eel caught in the Baltic Sea, Eustrongylides mergorum for German freshwaters, and Goezia anguillae from the Tagus estuary in Portugal. Special consideration was given to the distribution of the swimbladder nematode Anguillicola crassus . A map and table of first reported records of this neozoan parasite species for 25 countries as well as a survey map indicating all published localities documented in the checklist are provided.